Participatory Needs Assessment in Local Development: Rhetoric or Reality: A Case of Putalibazaar, Syangja - Bhandari, Amrit Kumar (Himalayan Journal of Sociology and Anthropology, 2012)
Based on the first hand data collected through fieldwork, this article highlights the rhetoric and reality of people’s participation in the local development activities in Putalibazaar Syangja. Concentrating on the foundational aspect of participatory development i.e. needs assessment, this article explains that the needs assessment program being practiced by Putalibazaar Municipality is weaker and ineffective one. In the name of participatory planning, there has been the domination of the leader-centric approach as opposed to the people-centric one in needs assessment. Thus, this article posits that people’s participation in development activities in Putalibazaar is more rhetoric than reality. DOI: http://dx.doi.org/10.3126/hjsa.v5i0.7035 Himalayan Journal of Sociology & Anthropology-Vol. V (2012) 1-9